Membaca Konflik Dan Relasi Kuasa Pada Masyarakat Menengah Religius-Industrialis : Studi Pembacaan Fenomena Konflik Versi Marx, Coser, Dan Dahrendorf - Muhammad Farhan; Syamsul Arifin (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
The middle class was born from the dichotomy of conflict between capitalists and workers. This middle class is faced with the fact that they are faced with vertical and horizontal class interests. On the one hand, they are faced with pressure from capitalist groups, while on the other hand, they are faced with proletarian class competition. In addition, the middle class is prone to stuttering transformation between the sacred (religion) and profane (industry) areas. This study reads a phenomenon of inequality in the transformation of a religious-industrial middle class group in Penampon Village, Pasuruan. This study aims to provide a theoretical interpretation of the social phenomena that occur. While as a practical goal, this study attempts to provide a scientific explanation to be used as reading material for the general public to become a reflective value. The type of data method used is observational and qualitative data description. Data sources were obtained through interviews with several informants. From this study, several conclusions were found, First, conflict must arise from interests, both vertical (bourgeois-proletarian) and horizontal (between bourgeois groups and between proletarians). Second, the religious-industrial middle class thinks about two separate latent problems, namely the problem of slow religious transformation and the rapid industrialization project. Third, the power can be born from the truth project. The truth project is latent and produced by the power holders who are based on their superior capital.